The microevolutionary trajectory of endemic multidrug-resistant tuberculosis strains in Portugal toward increased drug resistance levels and its clinical significance - Gomes, Pedro; Paixão, Paulo; Maltez, Fernando; Brum, Laura; Phelan, Jody E.; Campino, Susana; Clark, Taane G.; Viveiros, Miguel; Portugal, Isabel; Perdigão, João (Frontiers in Microbiology, 2026)
Portugal has one of the highest incidence rates of tuberculosis (TB) in Western Europe and, historically, multidrug-resistant (MDR) cases have been strongly associated with Mycobacterium tuberculosis strains pertaining to the endemic Q1 and Lisboa3 clades. Notwithstanding, the contribution of drug resistance-associated allelic configurations in these clades to differing levels of drug resistance and their relationship with drug efficacy has yet to be uncovered. A representative sample of the drug-resistant M. tuberculosis population in Portugal, comprised of 40 clinical strains were subjected to whole genome sequencing for characterization of allelic combinations of drug resistance-associated mutations and their minimum inhibitory concentrations for 12 anti-TB drugs was determined. Pharmacokinetic (PK) models were generated to ascertain the maximum concentration to which each drug remains efficacious. Drug resistance levels were determined and compared between different allelic configurations. Double inhA and embA/B mutation genotypes contributed with increased isoniazid and ethambutol resistance levels compared with single mutation configurations, respectively. Significant differences in drug resistance levels were observed between phylogenetic groups for rifamycin, streptomycin and ethionamide, largely explained by the presence/absence of unique high-level resistance-associated genotypes. The PK models for isoniazid and moxifloxacin suggest an increase in dosage to be ineffective against strains harboring high-level resistance-conferring double inhA mutations and gyrA/B mutations. Cycloserine and para-aminosalicylic acid are the only drugs predicted to remain efficacious against the majority of tested strains, while the effectiveness of newer drugs like bedaquiline, pretomanid and delamanid have yet to be uncovered. Proper diagnosis of drug resistance-associated mutations provides invaluable insights into the treatment of TB, as different allelic configurations lead to differing drug resistance levels, often rendering drugs ineffective.